Digital Islamic Finance, Halal Value Chains, and Financial Inclusion among Halal MSMEs in Aceh - Nur Syarifatul Isra; Malahayatie (Journal of Islamic Economic and Business Research, 2026)
This study examines the effect of Digital Islamic Finance on the Financial Inclusion of halal Micro, Small, and Medium Enterprises (MSMEs) in Aceh, Indonesia, with the Halal Value Chain serving as a moderating variable. The study aims to determine whether Digital Islamic Finance enhances access to formal financial services among halal MSMEs and whether the Halal Value Chain strengthens this relationship. A quantitative approach was employed using data collected from 300 halal MSMEs in Aceh. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships among the proposed constructs. The findings reveal that the Halal Value Chain has a positive and significant effect on Financial Inclusion and that Digital Islamic Finance positively influences the Halal Value Chain. However, Digital Islamic Finance does not directly affect Financial Inclusion. The moderation analysis indicates that the Halal Value Chain significantly strengthens the relationship between Digital Islamic Finance and Financial Inclusion. These results suggest that digital Islamic financial services are more effective in promoting financial inclusion when supported by a well-developed halal business ecosystem. This study contributes to the growing literature on Islamic finance and financial inclusion by providing empirical evidence from a regional Islamic economic context. The findings imply that policymakers should strengthen halal ecosystem development, while Islamic financial institutions should expand digital financial services tailored to halal MSMEs. In addition, MSME stakeholders are encouraged to enhance their integration into halal value chain networks to improve access to formal financial services and support sustainable business growth.